Screening of Five Lamiaceae Essential Oils as Repellents for Sweet Potato Weevil, Cylas Formicarius (F.) (Coleoptera: Brentidae) - Mai, Pham Thi; Ha, Hoang Thi Thanh; Suu, Bui Thi; Thao, Le Thi; Quyen, Nguyen Thi; Toan, Tran Dinh; Lien, Vu Thi; Rei, Yamakawa (Asian Journal of Agriculture and Rural Development, 2021)
In this research, the repellent activity of five Lamiaceae essential oils, Agastache rugosa, Elsholtzia blanda, Elsholtzia ciliata, Elsholtzia penduliflora, and Plectranthus ovatus, was evaluated against sweet potato weevil, Cylas formicarius using a two-choice test between the essential oil-treated filter paper and the control. E. blanda and A. rugosa essential oils have some sweet potato weevil attractant properties at low dose (<47.16 nl/cm2),while N,N-diethyl-3-methylbenzamide (DEET), P. ovatus, E. penduliflora, and E.ciliata essential oils have repellent properties at doses ranging from 15.72 nl/cm2 to 196.49 nl/cm2. The effect of type of essential oil and their dose were interactively associated with repellent efficacy. There was a increase in repellent efficacy as the dose increased for all essential oils. The repellent activities of P. ovatus essential oil and E. penduliflora were higher than the others, and the repellent effects of E. ciliata essential oil and DEET were more dose-dependent than others, indicating that at low dose, P. ovatus and E. penduliflora essential oils have stronger repellent efficacy, but at higher dose DEET and E. ciliata have greater effects. Our findings clearly demonstrate that P. ovatus, E. penduliflora, and E. ciliata essential oils are candidate materials for future investigation as repellent compounds against sweet potato weevil control.